Tstraw Company / Nur Izzi Idris … [et al.] - Idris, Nur Izzi; Zakaria, Nurul Syafiqah; A.Rahman, Nur Alia Farhana; Kamalrozaman, Nur Aimie Kamalia; Nik Shamlan, Nik Shaheera Azfareeda (2022)
Tstraw is a partnership business comprising five partners. All partners hold five key positions in the business namely General Manager, Administrative Manager, Marketing Manager, Operations Manager and Finance Manager. The partnership was established on November 20, 2021. Tstraw financed the business using personal contributions from partners amounting to RM 50,000 each and from bank loans. All partner contributions and bank loans are used to support the capital and expenses of our start -up business. We also plan to use the funds to purchase all the equipment to operate the business. Tstraw Company conducts its business in Section 14, Petaling Jaya, Selangor. This location was chosen because it is surrounded by shopping mall area and this area is an easily accessible area as there are many public vehicles. The concept of this business is to supply biodegradable straw to customers in addition to providing high quality consumer -friendly and environmentally friendly products. The uniqueness of our business is that Tstraw provides three types of straws with different materials that we called them as Straw Troopers. The types of straw we provide are stainless steel, bamboo and glass. All types of straws will be packed together with a clean brush in the small pouches. Tstraw ensure that the package must be easy for customers to take anywhere. This location is said to be strategic because it is close to restaurants and also housing estates. Therefore, Tstraw’s target market is any restaurants and residential areas that need biodegradable straw around Petaling Jaya. Through research, there are many restaurants operating around here and in addition there are no straw suppliers around here. So Tstraw believes we will be able to stabilize ourselves by focusing on this target market. In addition, Tstraw also provides delivery services for the convenience of customers and also give them discounts. With the increasingly sophisticated age, customers can also find Tstraw products online. Although Tstraw has no closest competitors but because this business is a newly established business, Tstraw still has possible competition where people around are more comfortable with the product than existing straw competitors in the market. So Tstraw took the time to build a business to conquer the market. We believe we are able to compete with competitors because we have been able to identify the weaknesses of competitors that we are able to overcome.